A method for preparing sodium trititanate nanofiber
By using high dispersion equilibrium and non-equilibrium hydrothermal methods in the preparation process of sodium trititanate nanofibers, the problems of uneven morphology and small aspect ratio in the traditional method are solved, and a more uniform morphology and higher aspect ratio are achieved.
Patent Information
- Application Number
- CN202310037829.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-10
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-01-10
AI Technical Summary
The existing preparation methods for sodium trititanate nanofibers lead to uneven morphology and small aspect ratios of the product.
Using the improved high-dispersion equilibrium hydrothermal method and high-dispersion non-equilibrium hydrothermal method, the aqueous sodium hydroxide solution and the ethanol solution of the titanium source are prepared in an ice water bath environment, and then mixed evenly and hydrothermal reaction is carried out in the polytetrafluoroline liner. The reaction conditions such as temperature, time and stirring speed are controlled to improve the uniform mixing and contact area of the reactants.
The morphological uniformity of sodium trititanate nanofibers was significantly improved, the aspect ratio of the fiber was improved, and the reaction time was shortened.
Smart Images

Figure CN116081681B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of material preparation, and in particular to a method for preparing sodium trititanate nanofibers. Background Art
[0002] One-dimensional nanostructured metal oxides have been widely used in electronic, optical and magnetic devices due to their structural characteristics. Na2Ti3O7 belongs to the monoclinic system and exhibits excellent performance in many aspects due to its unique layered structure. For example, layered sodium titanate materials have become one of the research hotspots of negative electrode materials for sodium ion batteries in recent years. As negative electrode materials, they have the advantages of low working voltage, stable structure, low cost and green environmental protection. For example, sodium titanate and its modified products have good performance in radiation resistance and thermal stability, fast adsorption kinetics and ion exchange capacity, and have great application scenarios in the field of element separation, such as the adsorption of heavy metal cesium or the removal of radioactive nuclides 60Co (II); for example, the one-dimensional nanostructure of Na2Ti3O7 is used as an n-type semiconductor, and it shows excellent photocatalytic activity, which can be used to couple carriers with other nano-modified materials (such as In2S3, GO, MWCNTs, Cds, etc.) to improve the visible light photocatalytic properties. In addition, sodium trititanate is widely used in coatings and pigments, ion exchange, microelectronics, composite materials, electroluminescence and other fields. It can be used as a plastic reinforcing agent, oxygen electrode for sensors, insulating resonator conveyor belts, insulating materials, etc.
[0003] At present, the main methods for synthesizing sodium trititanate nanofibers are: template synthesis method, template-free hydrothermal method, solid phase method (molten salt method), etc. Among them, the traditional hydrothermal method uses a solid phase titanium source, and the solid and liquid phases are difficult to mix evenly, and the powder particles are easy to agglomerate and settle, resulting in different reactant concentrations and pH concentrations in different areas of the reactor, and large differences in reaction rates. Therefore, the product Na2Ti3O7 has extremely uneven morphology and a small aspect ratio.
[0004] In summary, after extensive searching by the applicant, it is found that at least there is a problem in the art that the sodium trititanate nanofibers synthesized by the existing preparation methods have extremely non-uniform morphology and small aspect ratio. Therefore, it is necessary to develop or improve a preparation method for sodium trititanate nanofibers. Summary of the invention
[0005] Based on this, in order to solve the problem that the sodium trititanate nanofibers synthesized by the existing preparation method have extremely uneven morphology and small aspect ratio, the present invention provides a method for preparing sodium trititanate nanofibers, and the specific technical scheme is as follows:
[0006] A method for preparing sodium trititanate nanofibers comprises the following steps:
[0007] Step 1: In an ice water bath, prepare a sodium hydroxide aqueous solution and an ethanol solution of a titanium source respectively;
[0008] Step 2: in an ice water bath environment and under stirring, the sodium hydroxide aqueous solution and the ethanol solution of the titanium source are mixed uniformly to obtain a premixed solution;
[0009] Step 3: transferring the premixed liquid into a polytetrafluoroethylene liner, placing the polytetrafluoroethylene liner in a stainless steel reactor for hydrothermal reaction to obtain a pre-product;
[0010] Step 4: After cooling, the pre-product is washed until the pH is neutral, and dried to obtain the product sodium trititanate nanofibers.
[0011] Furthermore, the titanium source is tetrabutyl titanate and / or titanium isopropoxide.
[0012] Furthermore, the stirring time is 0.3 to 2 hours;
[0013] The stirring speed is 200-600 r / min.
[0014] Furthermore, the concentration of the sodium hydroxide aqueous solution is 8-12M.
[0015] Furthermore, the concentration of titanium element in the ethanol solution of the titanium source is 0.1-0.4M.
[0016] Further, the temperature of the hydrothermal reaction is 180-220°C;
[0017] The hydrothermal reaction time is 4 to 20 hours.
[0018] Furthermore, the molar ratio of the sodium hydroxide to the titanium element in the titanium source is 100:0.83-5.
[0019] Furthermore, the hydrothermal reaction conditions also include simultaneous stirring, and the speed of the simultaneous stirring is 100 to 1000 r / min.
[0020] Furthermore, the solvent used for cleaning includes one or more of deionized water, ultrapure water and anhydrous ethanol;
[0021] The cleaning method includes one or more of stirring cleaning, suction filtration cleaning and ultrasonic cleaning.
[0022] Furthermore, the drying temperature is 60-100°C.
[0023] The above invention is based on the traditional hydrothermal method, and provides two technical solutions: the improved high-dispersion equilibrium hydrothermal method and the high-dispersion non-equilibrium hydrothermal method. The uniformity of the prepared Na2Ti3O7 fiber morphology is greatly improved, and the aspect ratio is greatly improved. Among them, the high-dispersion equilibrium hydrothermal method disperses the liquid titanium source into the solvent to form a low-viscosity solution with molecular level uniformity, and after mixing with the alkaline solution, it forms a sol system with greatly improved dispersibility. The solid and liquid phases are evenly mixed and the contact area is greatly improved. Therefore, it can greatly improve the uniformity of the product morphology, improve the aspect ratio and shorten the reaction time. The high-dispersion non-equilibrium hydrothermal method is based on the equilibrium state, and the equilibrium state spontaneously formed during the reaction process is changed to a non-equilibrium state formed by high-speed stirring, so as to prevent the sol system from being in the equilibrium state for a long time and sedimentation, further improve the dispersibility of the sol system, and make the contact between the reactants more sufficient and uniform. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a scanning electron microscope image of sodium trititanate nanofiber sample 3 prepared by conventional hydrothermal method comparative example 1;
[0025] Figure 2 is the X-ray diffraction spectrum of the sodium trititanate nanofiber sample 3 prepared by the conventional hydrothermal method comparative example 1;
[0026] Figure 3 is a scanning electron microscope image of the sodium trititanate nanofiber sample 1 prepared by the equilibrium hydrothermal method Example 1;
[0027] Figure 4 is the X-ray diffraction spectrum of the sodium trititanate nanofiber sample 1 prepared by the equilibrium hydrothermal method Example 1;
[0028] Figure 5 is a scanning electron microscope image of the sodium trititanate nanofiber sample 2 prepared by the non-equilibrium hydrothermal method Example 2;
[0029] Figure 6 is a scanning electron microscope image of the sodium trititanate nanofiber sample 2 prepared by the non-equilibrium hydrothermal method Example 2;
[0030] Figure 7 It is the X-ray diffraction spectrum of sodium trititanate nanofiber sample 2 prepared by non-equilibrium hydrothermal method Example 2. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with its embodiments. It should be understood that the specific implementation methods described herein are only used to explain the present invention and do not limit the protection scope of the present invention.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0033] A method for preparing sodium trititanate nanofibers in one embodiment of the present invention comprises the following steps:
[0034] Step 1: In an ice water bath, prepare a sodium hydroxide aqueous solution and an ethanol solution of a titanium source respectively;
[0035] Step 2: in an ice water bath environment and under stirring, the sodium hydroxide aqueous solution and the ethanol solution of the titanium source are mixed uniformly to obtain a premixed solution;
[0036] Step 3: transferring the premixed liquid into a polytetrafluoroethylene liner, placing the polytetrafluoroethylene liner in a stainless steel reactor for hydrothermal reaction to obtain a pre-product;
[0037] Step 4: After cooling, the pre-product is washed until the pH is neutral, and dried to obtain the product sodium trititanate nanofibers.
[0038] In one embodiment, the titanium source is tetrabutyl titanate and / or titanium isopropoxide. Preferably, the titanium source is tetrabutyl titanate.
[0039] In one embodiment, the stirring time is 0.3 to 2 hours;
[0040] The stirring speed is 200-600 r / min.
[0041] Preferably, the stirring time is 0.3 to 1 h;
[0042] The stirring speed is 200-600 r / min.
[0043] Further preferably, the stirring time is 0.3 to 1 h;
[0044] The stirring speed is 300-600 r / min.
[0045] In one embodiment, the concentration of the sodium hydroxide aqueous solution is 8 to 12 M. Preferably, the concentration of the sodium hydroxide aqueous solution is 9 to 12 M. More preferably, the concentration of the sodium hydroxide aqueous solution is 9 to 11 M.
[0046] In one embodiment, the concentration of titanium element in the ethanol solution of the titanium source is 0.1-0.4M.
[0047] In one embodiment, the temperature of the hydrothermal reaction is 180-220°C;
[0048] The hydrothermal reaction time is 4 to 20 hours.
[0049] Preferably, the temperature of the hydrothermal reaction is 180-220°C;
[0050] The hydrothermal reaction time is 6 to 15 hours.
[0051] Further preferably, the temperature of the hydrothermal reaction is 190-210°C;
[0052] The hydrothermal reaction time is 6 to 15 hours.
[0053] In one embodiment, the molar ratio of the sodium hydroxide to the titanium element in the titanium source is 100:0.83-5. Preferably, the molar ratio of the sodium hydroxide to the titanium element in the titanium source is 100:1.5-4. More preferably, the molar ratio of the sodium hydroxide to the titanium element in the titanium source is 100:2.5-4.
[0054] In one embodiment, the hydrothermal reaction conditions also include simultaneous stirring, and the stirring speed is 100 to 1000 r / min. Preferably, the hydrothermal reaction conditions also include simultaneous stirring, and the stirring speed is 200 to 800 r / min. More preferably, the hydrothermal reaction conditions also include simultaneous stirring, and the stirring speed is 300 to 700 / min.
[0055] In one embodiment, the simultaneous stirring is carried out by magnetic stirring or mechanical stirring.
[0056] In one embodiment, the solvent used for cleaning includes one or more of deionized water, ultrapure water and anhydrous ethanol;
[0057] The cleaning method includes one or more of stirring cleaning, suction filtration cleaning and ultrasonic cleaning.
[0058] Preferably, the solvent used for cleaning includes deionized water and / or ultrapure water;
[0059] The cleaning method includes one or more of stirring cleaning, suction filtration cleaning and ultrasonic cleaning.
[0060] Further preferably, the solvent used for cleaning includes deionized water and / or ultrapure water;
[0061] The cleaning method includes suction cleaning and / or ultrasonic cleaning.
[0062] In one embodiment, the drying temperature is 60-100° C. Preferably, the drying temperature is 70-100° C. More preferably, the drying temperature is 70-90° C.
[0063] The embodiments of the present invention will be described in detail below with reference to specific examples.
[0064] Embodiment 1:
[0065] Example 1: Sodium trititanate nanofibers were prepared by a highly dispersed equilibrium hydrothermal method;
[0066] Preparation of sodium hydroxide aqueous solution: weigh 24 parts of sodium hydroxide by mass in a glove box, add ultrapure water, prepare a 10M sodium hydroxide aqueous solution in a beaker, and stir magnetically at 300 r / min in an ice water bath until it becomes clear;
[0067] Preparation of ethanol solution of titanium source: by volume, take 60 parts of ethanol and 4.08 parts of tetrabutyl titanate [CH3(CH2)3O]4Ti with a pipette and add them into a beaker, and ultrasonically disperse for 30 minutes to obtain a tetrabutyl titanate ethanol solution with a titanium element concentration of 0.2M;
[0068] The tetrabutyl titanate ethanol solution was placed in an ice-water bath and stirred, and a sodium hydroxide aqueous solution was added, and stirred at a speed of 500 r / min for 30 min to obtain a premixed solution;
[0069] The premixed solution was transferred to a 200 ml polytetrafluoroethylene liner, and the polytetrafluoroethylene liner was placed in a stainless steel reactor for hydrothermal reaction at 200° C. for 10 h in equilibrium state to obtain a pre-product;
[0070] After cooling to room temperature, the pre-product was filtered and washed with ultrapure water until the pH was neutral, and then dried at 80° C. to obtain the product sodium trititanate nanofibers, which is sample 1.
[0071] Embodiment 2:
[0072] Example 2: Preparation of sodium trititanate nanofibers using a highly dispersed non-equilibrium hydrothermal method;
[0073] Preparation of sodium hydroxide aqueous solution: weigh 24 parts of sodium hydroxide by mass in a glove box, add ultrapure water, prepare a 10M sodium hydroxide aqueous solution in a beaker, and stir magnetically at 300 r / min in an ice water bath until it becomes clear;
[0074] Preparation of ethanol solution of titanium source: by volume, take 60 parts of ethanol and 4.08 parts of tetrabutyl titanate [CH3(CH2)3O]4Ti with a pipette and add them into a beaker, and ultrasonically disperse for 30 minutes to obtain a tetrabutyl titanate ethanol solution with a titanium element concentration of 0.2M;
[0075] The tetrabutyl titanate ethanol solution was placed in an ice-water bath and stirred, and a sodium hydroxide aqueous solution was added, and stirred at a speed of 500 r / min for 30 min to obtain a premixed solution;
[0076] The premixed solution was transferred to a 200 ml polytetrafluoroethylene liner, and the polytetrafluoroethylene liner was placed in a stainless steel stirred reactor for hydrothermal reaction. The reaction temperature was set to 200° C., and magnetic stirring was performed at 500 r / min. The reaction was carried out in the non-equilibrium state for 10 h to obtain a pre-product.
[0077] After cooling to room temperature, the pre-product was filtered and washed with ultrapure water until the pH was neutral, and then dried at 80° C. to obtain the product sodium trititanate nanofibers, which is sample 2.
[0078] Comparative Example 1:
[0079] Comparative Example 1: Sodium trititanate nanofibers were prepared using a conventional hydrothermal method;
[0080] Preparation of sodium hydroxide aqueous solution: weigh 16 parts of sodium hydroxide by mass in a glove box, add ultrapure water, use a beaker to prepare a sodium hydroxide aqueous solution with a concentration of 10M, and stir magnetically at 300 r / min in an ice water bath until it becomes clear;
[0081] Weigh 2 parts of TiO2 by mass and add them into a beaker. Stir at 500 r / min for 30 min to obtain a mixed solution.
[0082] The mixed solution was transferred to a 50 ml polytetrafluoroethylene liner, and the polytetrafluoroethylene liner was placed in a stainless steel stirred reactor for hydrothermal reaction at 200° C. for 72 h to obtain a pre-product;
[0083] After cooling to room temperature, the pre-product was filtered and washed with ultrapure water, and then dried in a vacuum oven at 80° C. to obtain the product sodium trititanate nanofibers, which is sample 3.
[0084] Samples 1, 2 and 3 were subjected to electron microscope scanning and X-ray diffraction analysis. The results are as follows: Figures 1 to 6 shown.
[0085] like Figure 1 and Figure 2 As shown, the sodium trititanate sodium trititanate nanofibers prepared by the traditional hydrothermal method are basically short rods with poor morphology uniformity. The relatively long and thin fibers are 4.588um long, 130.5nm in diameter, and have an aspect ratio of 35. Their XRD diffraction peaks are completely consistent with the standard card PDF31-1329 of sodium trititanate Na2Ti3O7, proving that comparative example 1 prepared pure phase sodium trititanate nanofibers with poor morphology and low aspect ratio.
[0086] like Figure 3and Figure 4 As shown in the figure, the sodium trititanate sodium trititanate nanofibers prepared by the high-dispersion equilibrium hydrothermal method have a relatively more uniform morphology, with a fiber length of 12.15um, a diameter of 215.8nm, and an aspect ratio of 56; the product XRD diffraction peak is completely consistent with the standard card PDF 31-1329 of sodium trititanate Na2Ti3O7. It can be seen that the equilibrium hydrothermal method shortens the reaction cycle from 72h to 10h, and greatly improves the uniformity of the fiber morphology and the aspect ratio.
[0087] like Figure 5 As shown in the figure, the sodium trititanate sodium trititanate nanofibers prepared by the high-dispersion non-equilibrium hydrothermal method maintain the uniformity of morphology relative to the high-dispersion equilibrium state, while the fibers are longer and have a larger aspect ratio. Figure 6 (Probably due to the high-speed stirring and dispersion, a small amount of broken fibers were produced). The fiber length was 44.91 μm, the diameter was 297.7 nm, and the aspect ratio was as high as 150.8. Figure 7 The XRD diffraction peaks of the product are completely consistent with the standard card PDF 31-1329 of sodium trititanate Na2Ti3O7. It can be seen that the non-equilibrium hydrothermal method is more evenly dispersed than the equilibrium gel system, and the obtained sodium trititanate nanofibers have more uniform morphology and the aspect ratio is further greatly improved.
[0088] The traditional hydrothermal method uses a solid-phase titanium source and a liquid-phase alkaline solution to carry out a solid-liquid mixed reaction. The reaction rate is slow and the experimental cycle is long. At the same time, there is powder particle agglomeration and sedimentation, which leads to uneven product morphology and low aspect ratio. The present invention prepares uniform ultra-high aspect ratio sodium trititanate nanofibers by using a high-dispersion equilibrium hydrothermal method and a non-equilibrium hydrothermal method that improve the traditional hydrothermal method. The titanium source and the sodium hydroxide solution are uniformly mixed in a specific concentration range, and then transferred to a high-pressure reactor for equilibrium or non-equilibrium hydrothermal reaction after stirring, and then washed and dried to obtain. The raw materials used in the present invention are widely available, low in price, lower in energy consumption, simple in preparation process, short in preparation cycle, uniform in fiber morphology, and high in aspect ratio.
[0089] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0090] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing sodium trititanate nanofibers, characterized in that: It includes the following steps: Step 1: In an ice water bath environment, prepare a sodium hydroxide aqueous solution and an ethanol solution of a titanium source respectively, wherein the concentration of the sodium hydroxide aqueous solution is 8-12M; the concentration of the titanium element in the ethanol solution of the titanium source is 0.1-0.4M; the molar ratio of the sodium hydroxide to the titanium element in the titanium source is 100:0.83-5; Step 2: In an ice water bath environment and under stirring, and the stirring speed is 200-500 r / min, the sodium hydroxide aqueous solution and the ethanol solution of the titanium source are mixed uniformly to obtain a premixed solution; Step 3: transferring the premixed liquid to a polytetrafluoroethylene liner, placing the polytetrafluoroethylene liner in a stainless steel reactor for hydrothermal reaction, wherein the temperature of the hydrothermal reaction is 180-220° C., and the conditions of the hydrothermal reaction also include simultaneous stirring, and the speed of the simultaneous stirring is 500-1000 r / min, to obtain a preproduct; Step 4: After cooling, the pre-product is washed until the pH is neutral, and dried to obtain the product sodium trititanate nanofibers.
2. The preparation method according to claim 1, characterized in that: The titanium source is tetrabutyl titanate and / or titanium isopropoxide.
3. The preparation method according to claim 1, characterized in that: The stirring time is 0.3 to 2 hours.
4. The preparation method according to claim 1, characterized in that: The hydrothermal reaction time is 4 to 20 hours.
5. The preparation method according to claim 1, characterized in that: The solvent used for cleaning includes one or more of deionized water, ultrapure water and anhydrous ethanol; The cleaning method includes one or more of stirring cleaning, suction filtration cleaning and ultrasonic cleaning.
6. The preparation method according to claim 1, characterized in that: The drying temperature is 60-100°C.
Citation Information
Patent Citations
Method for treating water solution heavy metallic ion by using trititanic acid sodium whisker
CN101117729A
Preparation method of Na2Ti3O7 absorbing agent
CN102949983A